EFFECT OF SORTING AND SPACING ON THE GERMINATION OF COCONUT GROUND BED NURSERY - IBRAHIM, KOLOCHE MUSA; OLANREWAJU, ODUFALE OLADAPO; CHUKS, ADAIGBE VICTOR; ABDULRAHMAN, YAHAYA SADIQ; MUBO, ADEYEMI-AJIBULU ABIMBOLA (Innovare Journal of Agricultural Sciences, 2022)
Cultivation of coconut is deterred by unavailability of improved planting material. Reducing the quantity of un-germinated seed nuts will optimize nursery space as well as increase seedling production per cycle. The experimental design was randomized complete block with two treatments at two levels each and four replicates. Four hundred seed nuts were randomly selected while the remaining Four hundred were selected by sorting. The seed nuts were arranged in the seed beds in two treatment pattern “spaced” and “cluster” sowing methods with spacing of 30 cm by 30 cm and 5 cm by 5 cm, respectively. There was no significant difference between the spacing methods tested. As much as spacing is between 5 and 30 cm, the germination rate will be similar in ground bed nursery. There were differences in the germination parameters between the sorted and unsorted seed nuts. Sorting had significant effect on seed nut emergence 59.38A and 42.38B; p<0.05 for the unsorted and sorted, respectively. The number of days to emergence and germination was significant at 10% (84.50A; 72.72B), 25% (101.25A; 90.63B), and 50% (126.50A; 110.38B) for the unsorted and sorted respectively. The significant negative correlation coefficient (–0.56, p<0.05) between 50 and maximum germination (MGP) percentage indicated that sorted seed nuts attained 50% germination earlier than the unsorted ones. This will be effective in determining the duration of MGP percentage in the seed lots. Sorting before sowing is essential to ensure early germination of seed nuts and to achieve high germination percentage. It will as well save resources.